2015
DOI: 10.1111/iep.12154
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways regulate Cten in colorectal cancer without a Tensin switch

Abstract: CTEN/TNS4 is a member of the Tensin gene family. It localizes to focal adhesions and induces cell motility. The mechanisms regulating Cten expression are unclear although we have shown regulation by Kras in the colon and pancreas. In normal mammary cell lines, it is reportedly upregulated by epidermal growth factor receptor (EGFR) and STAT3 signalling and upregulation is accompanied by downregulation of Tensin 3 (Tensin switch). In this study, we investigated the roles of EGFR and STAT3 signalling in the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Downstream, differential binding to DLC1 induced cell motility through RhoA‐ROCK signalling . In CRC, and possibly cancer tissue in general, it is likely that alternative signaling mechanisms exist as firstly, we have not found no evidence of a tensin switch in CRC . Secondly, we found that DLC1 expression is often lost in CRC, suggesting that DLC1 is not a major player in Cten signaling.…”
Section: Introductionmentioning
confidence: 63%
“…Downstream, differential binding to DLC1 induced cell motility through RhoA‐ROCK signalling . In CRC, and possibly cancer tissue in general, it is likely that alternative signaling mechanisms exist as firstly, we have not found no evidence of a tensin switch in CRC . Secondly, we found that DLC1 expression is often lost in CRC, suggesting that DLC1 is not a major player in Cten signaling.…”
Section: Introductionmentioning
confidence: 63%
“…showing the role of Her2 in upregulating Cten in breast cancer cell lines. Furthermore, we and others have also found that Cten could be under the regulation of several cytokines such as IL6/Stat3 and growth factors, including EGF, NGF and FGF2 which also induces cell motility . The present study directly shows for the first time an essential role for Cten in TGF‐β1‐induced EMT and cell motility in CRC cells and that this may be through upregulation of the Src/ROCK1/Snail signalling pathway.…”
Section: Discussionmentioning
confidence: 70%
“…Further reports suggested that Cten is regulated by KRAS in both CRC and pancreatic cancer cells . Cten expression was also shown to be negatively regulated by STAT3 in CRC cell lines, whereas others have found that Cten is upregulated by STAT3 in human lung cancer cells . How Cten is activated and regulated in these tumours is unclear; nonetheless, multiple pathways seem to be involved, and it appears to be largely dependent on tissue type or context.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have suggested that Src protein stabilization is most likely to be induced through the up‐regulation of Akt/mTOR/4E‐BP1 pathways and inhibition of calpain‐mediated Src protein degradation by ErbB2 signaling . Cten has been shown to be induced by ErbB2 signaling and negatively regulated by calpain . One can conjecture that the ErbB2 pathway could protect Cten through calpain inhibition and this in turn could lead to Src protein stabilization.…”
Section: Discussionmentioning
confidence: 98%
“…Tensins localise to focal adhesions and absence of the capability to bind actin filaments is thought to be essential to the role of Cten . The importance of Cten is underscored by data showing that it is a common and functionally active target for a multitude of different signaling pathways …”
Section: Introductionmentioning
confidence: 99%